2010
DOI: 10.1080/00036840701604487
|View full text |Cite
|
Sign up to set email alerts
|

R&D intensity, firm performance and the identification of the threshold: fresh evidence from the panel threshold regression model

Abstract: This article tests whether there is an optimal level of research and development (R&D) intensity at which point a firm is able to maximize its performance. An advanced panel threshold regression model is employed to investigate the panel threshold effect of R&D intensity on firm performance among publicly traded Taiwan information technology and electronic firms. The results confirm that a single-threshold effect does exist and show an inverted-U correlation between R&D intensity and firm performance. This art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
65
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 66 publications
4
65
1
6
Order By: Relevance
“…Similar results are found in terms of R&D as indicator of sales growth, while it is claimed that the amount invested needs to surpass a certain benchmark to become effective (Morbey, 1988). More precisely, it is proposed that R&D intensity improves performance only up to a certain level of investment, while after a particular threshold, decreasing returns are expected (Yeh, Chu, Sher, & Chiu, 2010). Nevertheless, with respect to a study of the top spending European companies, higher levels of R&D investments are shown to lead to superior sales growth (Garciá-Manjoń & Romero-Merino, 2012).…”
supporting
confidence: 64%
See 2 more Smart Citations
“…Similar results are found in terms of R&D as indicator of sales growth, while it is claimed that the amount invested needs to surpass a certain benchmark to become effective (Morbey, 1988). More precisely, it is proposed that R&D intensity improves performance only up to a certain level of investment, while after a particular threshold, decreasing returns are expected (Yeh, Chu, Sher, & Chiu, 2010). Nevertheless, with respect to a study of the top spending European companies, higher levels of R&D investments are shown to lead to superior sales growth (Garciá-Manjoń & Romero-Merino, 2012).…”
supporting
confidence: 64%
“…The R&D intensity, also known as the R&D ratio, is a common measure in innovation studies (e.g. Yeh et al, 2010). Data for the R&D ratio was gathered from the annual EU R&D scoreboard (European Commission, 2017b) as previously done by Garciá-Manjoń and Romero-Merino (2012), in addition to ORBIS by calculating the figures manually.…”
Section: Cooperative Patent Classification (Cpc) or International Patmentioning
confidence: 99%
See 1 more Smart Citation
“…First, R&D is a costly activity that has a direct negative impact on a company's balance sheet, and an indefinite level of R&D investment does not necessarily yield proportional financial rewards (Yeh et al, 2010). There are several possible explanations for this result.…”
Section: Discussionmentioning
confidence: 99%
“…Most approaches have relied on measuring either a firm's improvement in productivity (Christoffersen, 2002) or financial performance (Andras & Srinivasan, 2003). The following determinants of Chinese textile firms' R&D effectiveness were examined: R&D intensity, external R&D, and internal R&D (Pike et al, 2005;Yeh et al, 2010). The following determinants of Chinese textile firms' R&D effectiveness were examined: R&D intensity, external R&D, and internal R&D (Pike et al, 2005;Yeh et al, 2010).…”
Section: Randd Effectivenessmentioning
confidence: 99%